ADMINISTRASI KELAS KELOMPOK TANI MADYA DI KECAMATAN TOMOHON BARAT KOTA TOMOHON - Patrecia M. Lapong; Jenny Baroleh; Benu Olfie (Universitas Sam Ratulangi, 2017)
ABSTRACT This study aims to determine the condition of administrative completeness of the middle class farmer groups in Tomohon Barat Subdistrict Tomohon City. The study was conducted from January to April 2017. Methods Data collection in this study using survey method. The data used in the primary data were obtained from direct interviews with farmer group members based on a prepared questionnaire. The sampling method in the middle farmer group in West Tomohon District was done purposively (purposive sampling, in the seven farmer groups in Tasatoma farmer group, Wahi Weru farmer group, Makaaruyen farmer group, Wongken Werun farmer group, farmer group Maju Bersama , Soko Meras Farmer Group, Ketu Sarang Farmer Group Of the seven farmer groups, three respondents were taken as chairman, secretary, and treasurer so that the number of samples was 21 people. Data analysis used in this research is descriptive analysis by using criteria: incomplete score 1, less complete score 2, and complete score 1. The results showed that the administration of activities, financial administration, and other administrative equipment in the middle farmer group in West Tomohon Sub-district not all run the administration based on existing provisions.Keywords : Administrative, class farmer groups, middle .